Search for charged Higgs bosons in e+e− collisions at √s=189-209 GeV - Abbiendi, Giovanni; Bock, Peter; Igo-Kemenes, Peter; Krogh, Jürgen von; Okpara, Anna (The European physical journal. C, Particles and fields, 2012)
A search is made for charged Higgs bosons predicted by Two-Higgs-Doublet extensions of the Standard Model (2HDM) using electron-positron collision data collected by the OPAL experiment at s√=189--209 GeVs=189--209 GeV\sqrt{s}=189\mbox{--}209\ \mbox{GeV}, corresponding to an integrated luminosity of approximately 600 pb−1. Charged Higgs bosons are assumed to be pair-produced and to decay into qq¯qq¯\mathrm{q} \bar{\mathrm{q}}, τν τ or AW±. No signal is observed. Model-independent limits on the charged Higgs-boson production cross section are derived by combining these results with previous searches at lower energies. Under the assumption BR(H±→τντ)+BR(H±→qq¯)=1BR(H±→τντ)+BR(H±→qq¯)=1\mathrm{BR} (\mathrm{H}^{\pm} \to \tau\nu_{\tau}) + \mathrm{BR} (\mathrm{H}^{\pm} \to \mathrm{q} \bar{\mathrm{q}}) = 1, motivated by general 2HDM type II models, excluded areas on the [mH±,BR(H±→τντ)][mH±,BR(H±→τντ)][m_{\mathrm{H}^{\pm}} , \mathrm{BR} (\mathrm {H}^{\pm} \to \tau\nu_{\tau})] plane are presented and charged Higgs bosons are excluded up to a mass of 76.3 GeV at 95 % confidence level, independent of the branching ratio BR(H±→τν τ ). A scan of the 2HDM type I model parameter space is performed and limits on the Higgs-boson masses mH±mH±m_{\mathrm{H}^{\pm}} and m A are presented for different choices of tanβ.